Bioskiving: Tendon-derived Scaffolds for Biomedical Applications. - Alberti, Kyle. (2017)
Abstract: The work contained herein is the development of a method to directly utilize the intricate and proven structures contained within tendon for biomedical applications ― a technique called Bioskiving. The hypothesize is that this sectioning-based technique will allow for maintenance of these structures while creating thin sheets that are flexible and can be formed into desired shapes. This fabrication process is applied to tendon, in order to capitalize on the mechanical and biological properties of the hierarchical and well-ordered collagen structures found within. This work progresses through the development of the processing technique and creation of scaffolds, which involves: decellularization, sectioning, and stacking and rolling to create two- and three-dimensional scaffolds. The mechanical properties of the material are then characterized, and tuned using crosslinking to achieve a 20-fold increase in mechanical strength and transverse isotropy. The biological properties of the material are also characterized, including the degradation in vitro and in vivo, and the interaction of the material with platelets. Lastly, one potential application of constructs comprised of the material is explored, peripheral nerve repair. The material's potential for nerve repair is evaluated in vitro using Schwann cells and chick dorsal root ganglia explants, and in vivo using a rat sciatic nerve defect model. The tendon-derived material proves to be a suitable substrate for promoting peripheral nerve repair, and is biocompatible and biodegradable. The mechanical properties can be tuned and the geometry of structures created be altered, allowing others to find use for it in a number of biomedical applications.; Thesis (Ph.D.)--Tufts University, 2015.; Submitted to the Dept. of Biomedical Engineering.; Advisor: Qiaobing Xu.; Committee: David Kaplan, Lauren Black, Barry Trimmer, and Bing Xu.; Keyword: Biomedical engineering.